Effect of corrosion inhibitors on internal corrosion in oil pipelines: a brief review - Esraa Razaq; Shaymaa Abbas Abdulsada (Zaštita Materijala)
The oil and gas industry primarily relies on pipelines to transport crude and refined petroleum, so transportation of crude oil is mostly handled by pipelines. In view of this, it is impossible to prevent the pipeline surfaces from being continuously exposed to corrosion sources, such as contaminants that contain traces of chromate and sulfur, which can cause corrosion to occur on the pipeline surfaces. It is known that corrosion inhibitors are chemicals that are used in low concentrations for the purpose of reducing or preventing corrosion.  The effectiveness of an inhibitor is determined by its ability to react with a metal's surface and produce a protective coating that reduces or prevents corrosion by reacting with the metal's surface. A review of corrosion mechanisms in oil pipelines is presented in this article, along with a description of how corrosion inhibitors can be selected according to the corrosion mechanisms in oil pipelines.